“Wars” on COVID-19 in Slovakia, Russia, and the United States: Securitized Framing and Reframing of Political and Media Communication Around the Pandemic - Lukacovic, Marta N. (Frontiers in Communication, 2020)
This study analyzes securitized discourses and counter narratives that surround the COVID-19 pandemic. Controversial cases of security related political communication, salient media enunciations, and social media reframing are explored through the theoretical lenses of securitization and cascading activation of framing in the contexts of Slovakia, Russia, and the United States. The first research question explores whether and how the frame element of moral evaluation factors into the conversations on the securitization of the pandemic. The analysis tracks the framing process through elite, media, and public levels of communication. The second research question focused on fairly controversial actors – “rogue actors” – such as individuals linked to far-leaning political factions or militias. The proliferation of digital media provides various actors with opportunities to join publicly visible conversations. The analysis demonstrates that the widely differing national contexts offer different trends and degrees in securitization of the pandemic during spring and summer of 2020. The studied rogue actors usually have something to say about the pandemic, and frequently make some reframing attempts based on idiosyncratic evaluations of how normatively appropriate is their government’s “war” on COVID-19. In Slovakia, the rogue elite actors at first failed to have an impact but eventually managed to partially contest the dominant frame. Powerful Russian media influencers enjoy some conspiracy theories but prudently avoid direct challenges to the government’s frame, and so far only marginal rogue actors openly advance dissenting frames. The polarized political and media environment in the US has shown to create a particularly fertile ground for rogue grassroots movements that utilize online platforms and social media, at times going as far as encouragement of violent acts to oppose the government and its pandemic response policy.